Early childhood stimulation interventions in developing countries: A comprehensive literature review - Helen Baker-Henningham; Florencia López Bóo (Institute for the Study of Labor (IZA), 2010)
This report reviews the effectiveness of early childhood stimulation interventions in developing countries. The report aims to answer the questions: What works in terms of early stimulation for young children in developing countries? For whom and under what conditions do these programs work and why do they work. The report is divided into several sections. Firstly, a brief discussion of the importance of early stimulation for young children in developing countries is provided. Secondly, the methods used to identify and characterize studies are provided and a review of randomized or quasi-experimental trials is presented. Thirdly, a review of the evidence for who benefits most from early interventions is presented followed by a review of program characteristics that affect the success of interventions and an examination of potential mechanisms through which interventions achieve their effects. Finally, recommendations for practice and future research are provided.
Keywords: J13; J18; J24; 330; child development; early stimulation; mothers; parenting; developing countries